Stakeholder relationship management and the perception of trust: a case study of a salient stakeholder - Chambers, Craig Brian (Rhodes University, Faculty of Commerce, Rhodes Business School)
Trust is an essential aspect in developing meaningful relationships between firms and their stakeholders. Mayer, Davis and Schoorman (1995, p.709) define trust as "the willingness of a party to be vulnerable to the actions of another party based on the expectation that the other party will perform a particular action important to the trustor irrespective of the ability to monitor or control that other party" . This study took the form of an explanatory case study that focussed on an interaction between a firm and a salient stakeholder and attempted to explain how this interaction influenced the perceived trustworthiness of the firm in stakeholders that were observing the interaction. The study attempted to add to the work of Crane (2020), whose research had focussed on stakeholder connectedness, and specifically how this could be utilized by firms interacting with stakeholders to engender trust in a wider group of stakeholders. The research aimed to evaluate how the Sterile Insect Release programme, operating by the firm in the Sunday's River Valley, was given a second chance through engagement with a salient stakeholder and how the interaction was observed by a wider group of stakeholders leading to perceived stakeholder trustworthiness and social capital. The study had five objectives, namely to; (1) analyse how a firm's ability, benevolence, and integrity enables (or does not engender) the development of the firm's trustworthiness amongst its stakeholders; (2) analyse how the firm's engagement with a salient stakeholder enables (or does not engender) increased levels of trustworthiness in the firm by the stakeholders that are observing its interaction with a salient stakeholder; (3) analyse the benefits of social capital gained through increased levels of stakeholder trust; (4) identify good practice guidelines for firm engagement with salient stakeholders to ensure the correct cues are portrayed to observing stakeholders for the development of the trustworthiness of the firm; and (5) make recommendations related to management practices that will support the development of trust. The research adopted a qualitative approach and data were collected through semi-structured interviews with three groups of stakeholders that were present at the meeting. A review of the literature was undertaken to identify various propositions for the research and from which a theory-driven coding memo was developed. The derived propositions were as follows: (1) observing a firm's engagement with a single salient stakeholder will provide cues to observing stakeholders about the trustworthiness of the firm, and (2) perceptions of a firm's trustworthiness will result in increased social capital between the firm and its stakeholders. The first proposition was divided into three sub-propositions for the study which stated; (a) observing a firm's engagement with a single salient stakeholder will provide cues to observing stakeholders about the ability of the firm; (b) observing a firm's engagement with a single salient stakeholder will provide cues to observing stakeholders about the benevolence of the firm; and (c) observing a firm's engagement with a single salient stakeholder will provide cues to observing stakeholders about the integrity of the firm. From the literature analysis, various themes were identified which include, observed interactions, ability, benevolence, integrity, trustworthiness, and increased social capital. The research findings confirmed the propositions as being relevant to the case study. The findings confirmed that ability, benevolence, and integrity are key attributes in portraying trustworthiness when interacting with a salient stakeholder. All three attributes were noted by the interviewees as being important to observing stakeholders in the development of trust in a firm, although ability and integrity were found to be the dominant attributes in this case study. The findings did present some evidence that an increased level of perceived trustworthiness in the firm did positively influence the levels of social capital, however, this was not a common theme among all the interviewees. In the light of these findings, it is recommended that firms utilize stakeholder models to identify salient stakeholders that are influential within the markets in which they operate. The firm should actively pursue a strong relationship with these stakeholders, and further attempt to generate opportunities to interact with these stakeholders in a public forum where stakeholder connectedness could be utilized to develop perceived trust in the wider group of stakeholders. The firm should focus on open, honest, and transparent communication which are key aspects for portraying the attributes of ability, benevolence, and integrity. The study addresses a gap in the trust literature at a stakeholder level and therefore has contributed to the trust literature by addressing how the connectedness between stakeholders can lead to trust in a wider group of stakeholders by increasing efficiency during these interactions and utilizing situational circumstances to build social capital.
Keywords: Stakeholder management -- South Africa Sundays River (Eastern Cape); Stakeholder theory; Trust; Industrial priorities; Social capital (Sociology)